An Overview on Indications and Chemical Composition of Aromatic Waters (Hydrosols) as Functional Beverages in Persian Nutrition Culture and Folk Medicine for Hyperlipidemia and Cardiovascular Conditions - Azadeh Hamedi PhD; Seyed Mahmoud Moheimani PharmD; Amirhossein Sakhteman PhD; Hamed Etemadfard MPhil; Mahmoodreza Moein PhD (SAGE Publishing, 2017)
Hydrosol beverages in Persian nutrition culture and ethnomedicine are the side products of essential oil industry that are used as delicious drinks or safe remedies. To investigate indications and chemical composition of hydrosol beverages for hyperlipidemia and cardiovascular conditions, Fars province was selected as the field of study. Ethnomedical data were gathered by questionnaires. The constituents of hydrosols were extracted with liquid/liquid extraction and analyzed by gas chromatography-mass spectrometry. Statistical analysis were used to cluster their constituents and find the relevance of their composition. A literature survey was also performed on plants used to prepare them. Thymol was the major or second major component of these beverages, except for wormwood and olive leaf hydrosols. Based on clustering methods, although some similarities could be found, composition of barberry, will fumitory, dill, and aloe hydrosols have more differences than others. These studies may help in developing some functional beverages or new therapeutics.